Peran Modal Sosial Sebagai Mediator Literasi Keuangan dan Inklusi Keuangan Pada Kaum Muda di Indonesia (Studi Kasus pada Komunitas Investor Saham Pemula) - Rachmat Simbara Saputra; Andrieta Shintia Dewi (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2017)
Currently the level of financial literacy and financial inclusion in Indonesian people, especially the younger generation, is still considered very low. Therefore, the role of social capital for improving financial literacy and financial inclusion in society need special attention. Social capital is expected to become a mediator for improving financial literacy and financial inclusion. This study aims to decide the role of social capital as a mediator of the relationship between financial literacy and financial inclusion. In addition, this study also examined the direct effect of financial literacy on financial inclusion. The population of this study were all members of the Investor Saham Pemula Community a number of 320 members. Making sample of this research using non-probability sampling technique with a sample size of 180 samples. This study adopts and uses Sobel and Kenny and Baron test to test the effect of mediation of social capital in the relationship between financial literacy and financial inclusion. The finding in this study is a proven social capital mediates the relationship between financial literacy and financial inclusion and there are no direct effect between financial literacy and financial inclusion.